Venice and Venetia under the Habsburgs, 1815-1835 - Laven, David (Oxford University Press, 2002)
The Austrian domination of Venice and Venetia after the Congress of Vienna has traditionally received a bad press. This volume questions this view, arguing from detailed archival research that Francis I's rule brought many real benefits to his Venetian subjects.